2018
DOI: 10.1007/s00018-018-2882-0
|View full text |Cite
|
Sign up to set email alerts
|

Viral journeys on the intracellular highways

Abstract: Viruses are obligate intracellular pathogens that are dependent on cellular machineries for their replication. Recent technological breakthroughs have facilitated reliable identification of host factors required for viral infections and better characterization of the virus-host interplay. While these studies have revealed cellular machineries that are uniquely required by individual viruses, accumulating data also indicate the presence of broadly required mechanisms. Among these overlapping cellular functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 258 publications
(349 reference statements)
1
71
0
1
Order By: Relevance
“…When hiding, the virus may either replicate in the host cell, or just be carried in an intracellular compartment of the circulating host cell. This latter strategy, however, is also hazardous for the virus, as the particles will need to escape the cell later on to disseminate, while avoiding being directed toward degradative endolysosomes [ 27 ]. Nevertheless, an associated benefit from subverting a blood cell is the possibility to hitch a ride incognito over long distances, opening the door to long-range dissemination.…”
Section: Disseminating Using a Trojan Horsementioning
confidence: 99%
“…When hiding, the virus may either replicate in the host cell, or just be carried in an intracellular compartment of the circulating host cell. This latter strategy, however, is also hazardous for the virus, as the particles will need to escape the cell later on to disseminate, while avoiding being directed toward degradative endolysosomes [ 27 ]. Nevertheless, an associated benefit from subverting a blood cell is the possibility to hitch a ride incognito over long distances, opening the door to long-range dissemination.…”
Section: Disseminating Using a Trojan Horsementioning
confidence: 99%
“…As is well known, many viruses hijack cellular machinery via host-pathogen interactions to function in their replicative cycles (Robinson et al 2018). To better understand the biological significance of the host proteins ending up in mature rabies virions, functional predictions of the 49 virion-packaged cellular proteins were performed according to the Gene Ontology Database.…”
Section: Analysis Of Virion-packaged Host Proteins Involved In Rabv Imentioning
confidence: 99%
“…These results collectively suggest that autophagy plays diverse roles in virus-host interactions by promoting viral replication via supporting membranous compartments, degrading infectious viruses via xenophagy, enhancing antiviral immunity by enhancing MHC-mediated antigen presentation, protecting infected cells from death and triggering viral infection induced by the elimination of T lymphocytes [9,11,13,395,396,397]. In the late 2000s, numerous studies demonstrated that autophagy is induced by Flaviviridae , among which HCV and DENV were the first shown to activate autophagy and thus benefit the viral life cycle [398,399,400]. To date, nearly one hundred studies have investigated the role of flavivirus-infected autophagy in the viral life cycle and host cell responses.…”
Section: Flavivirus-autophagy Interactionsmentioning
confidence: 99%